2006
DOI: 10.1248/bpb.29.527
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gatifloxacin on Serum Glucose Concentration in Normal and Diabetic Rats

Abstract: To clarify the mechanisms of gatifloxacin (GFLX)-induced hypoglycemia and hyperglycemia, the effect of GFLX on serum glucose levels was investigated in normal and diabetic rats. Rats received an intravenous injection of GFLX and their arterial blood was sampled periodically. Diabetic rats were produced by the intraperitoneal injection of streptozotocin and nicotinamide. In normal rats, the serum glucose concentration was decreased by GFLX at 25 and 50 mg/kg, while it was elevated 0.25 h after the injection of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 22 publications
3
27
0
1
Order By: Relevance
“…However, it must be noted that the hypoglycemias mostly occur at the beginning of a fluoroquinolone therapy [38], whereas after several days of therapy, when different intracellular accumulation may be more important, hyperglycemias are more frequent. While hyperglycemias may involve extrapancreatic effects [39], our observation that the fluoroquinolones at 100 µM were ineffective to stimulate insulin secretion in the presence of a basal glucose concentration leads to the provocative question why these compounds are hypoglycemic at all. Intriguingly, diabetes is a strong risk factor, independently of a sulfonylurea or insulin therapy [40] In conclusion, it seems that the K ATP channel-blocking effect is a necessary but not a sufficient condition for the hypoglycemic side effect of the fluoroquinolones.…”
Section: Correlation With Risk Of Hypoglycemiamentioning
confidence: 99%
“…However, it must be noted that the hypoglycemias mostly occur at the beginning of a fluoroquinolone therapy [38], whereas after several days of therapy, when different intracellular accumulation may be more important, hyperglycemias are more frequent. While hyperglycemias may involve extrapancreatic effects [39], our observation that the fluoroquinolones at 100 µM were ineffective to stimulate insulin secretion in the presence of a basal glucose concentration leads to the provocative question why these compounds are hypoglycemic at all. Intriguingly, diabetes is a strong risk factor, independently of a sulfonylurea or insulin therapy [40] In conclusion, it seems that the K ATP channel-blocking effect is a necessary but not a sufficient condition for the hypoglycemic side effect of the fluoroquinolones.…”
Section: Correlation With Risk Of Hypoglycemiamentioning
confidence: 99%
“…Tomita et al [19] reported that GFLX induced insulin oversecretion in the short-term, and decreased insulin productivity or increased insulin disintegration in the long-term using the insulin-secreting cell line HIT-T15. Based on the in vivo studies, Ishiwata et al [10] reported that serum glucose concentrations decreased and increased in normal and streptozotocin-induced diabetic rats, respectively, given a single intravenous injection of GFLX at 50 mg/kg, with elevations in both serum insulin and epinephrine (adrenaline) concentrations. However, few reports have dealt with the clinicopathological process of hypoglycemia or hyperglycemia induced by GFLX after repeated oral administration using the identical animals.…”
mentioning
confidence: 99%
“…25 mg/kg, as a single oral dose, for the study. 9 Oral suspension of the drug was made in 2% gum acacia and dose was adjusted to a volume of 2-5 ml daily for albino rabbits, which was administered with the help of a feeding catheter. Study medication was administered to the fasting animals after drawing samples for baseline values.…”
Section: Methodsmentioning
confidence: 99%
“…9 Reports also mention that, in patients with type 2 diabetes mellitus, gatifloxacin caused an increase in S. insulin 1 hour after its administration at a conventional dose (i.e. 400 mg once daily), with a downward trend in the FBS level.…”
Section: Non Diabetic Rabbitsmentioning
confidence: 99%